Resolving Hibah Disputes Involving Shared Property - Hotnidah Nasution; Ahmad Rifqi Muchtar (Jurnal Cita Hukum, 2023)
In the Islamic legal context, hibah has both worship and economic aspects. However, its practice often leads to problems when one or more terms determined by Islamic teachings are ignored. Among the violations in grant practice is granting hibah from property not fully owned by grantor. This paper aims to examine issues in resolving disputes on hibah (property granting) involving a shared property owned by a husband and wife. This study focuses on the examination of two judicial verdicts issued by the Religious Court (Verdict No.354 /Pdt.G/2022/PA.Pt) and the Appellate Religious Court (Verdict No. 222/Pdt.G/2022/PTA. SMG) on hibah dispute where hibah property contains shared property. This study finds that there are two approaches used by the judges in dealing with the issue. First, in the first instance court considered hibah void and revoked hibah. Similarly, the appellate court annulled hibah transaction but considered some part of the property to be rightful for grant. This is because hibah is taken from the property owned by grantor, which has been separated by his wife's property.